2022
DOI: 10.1002/ctm2.1137
|View full text |Cite
|
Sign up to set email alerts
|

RNA‐methyltransferase Nsun5 controls the maternal‐to‐zygotic transition by regulating maternal mRNA stability

Abstract: Background RNA modification‐induced ovarian dysgenesis appears to be necessary for ovary development. However, how m 5 C (5‐methylcytosine)‐coordinating modificatory transcripts are dynamically regulated during oogenesis, and ovarian development is unknown. The purpose of this study was to determine whether NOP2/Sun RNA methyltransferase 5 (Nsun5) deletion leads to suppression of ovarian function and arrest of embryonic development. The regulation of mRNA decay and stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…As a famous m6A “reader”, IGF2BP2 was confirmed to enhance mRNA stability and translation through its recognition of m6A modifications, and involve in the occurrence and development of various malignancies [ 47 ]. NSUN5 is one of the classical m5C methyltransferase, and it was reported to control the maternal-to-zygotic transition by regulating the translation efficiency of MAD2L2 and GDF9 in an m5C-dependent manner [ 48 ]. Strikingly, MeRIP-qPCR and RNA-stability assays also indicated that GPX4 was directly regulated by RBM15B- and IGFBP2 - mediated m6A modification and NSUN5-mediated m5C modification.…”
Section: Discussionmentioning
confidence: 99%
“…As a famous m6A “reader”, IGF2BP2 was confirmed to enhance mRNA stability and translation through its recognition of m6A modifications, and involve in the occurrence and development of various malignancies [ 47 ]. NSUN5 is one of the classical m5C methyltransferase, and it was reported to control the maternal-to-zygotic transition by regulating the translation efficiency of MAD2L2 and GDF9 in an m5C-dependent manner [ 48 ]. Strikingly, MeRIP-qPCR and RNA-stability assays also indicated that GPX4 was directly regulated by RBM15B- and IGFBP2 - mediated m6A modification and NSUN5-mediated m5C modification.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of this m 5 C site upswell increased during evolution; higher animals gained many NSUN2-mediated at mRNA 5′ ends, whereas humans were unique in acquiring thousands of NSUN6-mediated sites across the CDS and UTR regions ( Liu et al 2022 ). NSUN5 sites were also present in data from human oocytes ( Liu et al 2023 ), and in mice, NSUN5 was shown to be involved in oocyte function through mRNA modification ( Ding et al 2022 ).…”
Section: Physiological and Pathological Functions Of M 5 ...mentioning
confidence: 96%
“…[203][204][205][206]. Additionally, RNA epitranscriptomes significantly impact oocyte quality [207][208][209][210][211][212][213]. The epigenome of oocytes changes with age, potentially contributing to the decline in oocyte quality associated with aging [206,[214][215][216][217][218].…”
Section: Epigenetic Inheritance Of Energy Metabolism In Aging Oocytesmentioning
confidence: 99%